Cerebral Haemorrhage in a Young Patient With Atypical Werner Syndrome Due to Mutations in LMNA - Yanhua, Xiao; Suxian, Zhou (Frontiers in Endocrinology, 2018)
Introduction: Werner syndrome is a rare genetic disorder; classical Werner syndrome is caused by mutations in the WRN gene. However, recent research has shown that LMNA gene mutations can also cause premature ageing syndromes such as atypical Werner syndrome (AWS). AWS usually manifests as muscular damage, defects in the cardiac conduction system, lipoatrophy, diabetes, atherosclerosis, and premature ageing. Clinical presentation: A 24-year-old man presented with severe abdominal aortic and peripheral artery disease and cerebral haemorrhage. He was prescribed once-daily 20 mg atorvastatin. Another large cerebral haemorrhage occurred 8 months after discharge. Although he underwent minimally invasive intracranial haematoma surgery, paralysis set in. Molecular studies showed a missense mutation within exon 5 (c.898G>C) that caused amino acid aspartate 300 to be replaced by histidine (p.Asp300His) in the LMNA gene. The patient was diagnosed with AWS. Conclusions: Haemorrhagic stroke and progeroid features may be manifestations of LMNA-linked AWS. In such cases, the patient's family history and genetic background should be investigated. WRN and LMNA gene testing of the proband and the immediate family should be considered. This case report provides a deeper understanding of the role of LMNA mutations in AWS.